Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Usaha Toreko - Deva Safitri; Juliana Kadang; Ihksan Syarifuddin (Student Scientific Creativity Journal, 2023)
This study aims to determine the effect of brand image and product quality on purchasing decisions on Toreko’s product. The research method used is a qualitative description approach. The type of data is secondary data. The data collection method is to collect materials taken from previous related studies. The results showed that brand image and product quality had a positive and significant effect on purchasing decisions in Toreko's business.